Northeast ern Popular Puppet Theater - Mamulengo, Babau, João Redondo and Cassimiro Coco: an intangible Brazilian heritage (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article discusses the basic principles, guidelines and processes for theregistration of Northeast ern Popular Puppet Theater - Mamulengo, Babau, João Redondo and Cassimiro Coco - as part of Brazil’s cultural heritage. The article is based on a dossier, which is one of the requirements of IPHAN (National Institute of Historical and Artistic Heritage) to obtain the above-mentioned title.Keywords: Northeast ern popular puppet theater. Intangible heritage. Brazilian culture.